2020
DOI: 10.1080/19942060.2020.1745890
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on void fraction wave of reciprocating multiphase pumps with high gas rates based on real gas models

Abstract: Instantaneous gas-liquid flow and distribution have an important influence on the performance of a multiphase pump, especially under the high gas content conditions. How to accurately simulate the complete working cycle of a multiphase pump and reflect the transient oil-gas flow inside the pump cavity are the main difficulties of the study. A three-dimensional whole-cycle numerical simulation has been conducted to predict the void fraction waves of the reciprocating multiphase pumps under the high gas rates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…It can be found from Fig. 19a that most of the liquid during the compression process is accumulated under the discharge port, which leads to the higher pressure under the discharge port than that of (13) Figure 20 shows the variations of the pressure in the cylinder of the rotary compressor and the reciprocating compressor with crank angle under the same operating conditions.…”
Section: Effects Of Compressor Type On Two-phase Compression In the C...mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found from Fig. 19a that most of the liquid during the compression process is accumulated under the discharge port, which leads to the higher pressure under the discharge port than that of (13) Figure 20 shows the variations of the pressure in the cylinder of the rotary compressor and the reciprocating compressor with crank angle under the same operating conditions.…”
Section: Effects Of Compressor Type On Two-phase Compression In the C...mentioning
confidence: 99%
“…The results showed that liquid presence in the cylinder may cause up to five times the normal pressure on the compressor. Ma 13 simulated the transient liquid distribution and pressure fluctuation in the cylinder of reciprocating multiphase pump with different gas models and gas fractions. Through the calculations and experimental analysis, the impacts of liquid slugging on the reciprocating compressor can be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…The turbulence model is the key factor that affects the accuracy of CFD simulation for multiphase pumps, but there is no unified model [52,53]. At present, the two-equation models are usually adopted to predict the gas-liquid flow in the pump, which includes k-ε [25,[54][55][56], RNG k-ε [57][58][59] and SST k-ω [27,[60][61][62][63] models. The information on these three turbulence models and their application to the flow prediction in the multiphase pump are summarized in Table 3 [64].…”
Section: Turbulence Modelmentioning
confidence: 99%
“…Hydraulic pump is the core component of hydraulic equipment, known as the "heart" of the hydraulic system, and according to statistics, the pump industry consumes about 20 percent of electrical energy, is the second-largest electromechanical industry in the world [4][5][6][7]. Reciprocating piston pump (RPP) has the characteristics of large power density and ultimate high pressure, at first mainly used in large ships, water conservancy and hydropower and oil, mining fields [8,9]. With the aggravation of energy and environmental problems, RPPs are increasingly widely used in automobiles, engineering machinery, mobile machinery and stationary machinery.…”
Section: Introductionmentioning
confidence: 99%